Hindfoot flexibility influences the biomechanical effects of laterally wedged insoles and ankle-foot orthoses in medial knee osteoarthritis - Bartsch, Leonie P.; Schwarze, Martin; Block, Julia; Alimusaj, Merkur; Hadzic, Anela; Renkawitz, Tobias; Wolf, Sebastian Immanuel (Archives of physical medicine and rehabilitation, 2022)
Objective - To investigate the relationship of frontal plane ankle mobility with the effects of an ankle-foot orthosis (AFO) and a laterally wedged insole (LWI) on knee adduction moment (KAM) in the treatment of medial knee osteoarthritis. - Design - Randomized, nonblinded crossover trial. - Setting - Outpatient clinic of university hospital. - Participants - Referred sample of 20 patients (N=20) with medial knee osteoarthritis stage 1-3 (Kellgren and Lawrence), aged 56.4±6.5 years; 58 patients were assessed, 21 were included, and 1 was a dropout. There were 14 healthy reference participants without knee osteoarthritis (convenience sample) who were matched by age. - Interventions - Patients received AFO and LWI for 6 weeks each with gait analysis after each 6-week intervention. Patients underwent additional barefoot gait analysis, walking on even ground and on a cross slope of 5° lateral elevation and standing on inclinations of 0°, 5°, 10°, and 20°. - Main Outcome Measures - Spearman correlation between the immediate change in first peak of KAM with each aid and the change in hindfoot varus on the cross slope relative to level ground. - Results - The KAM reduction with AFO correlated significantly with hindfoot varus reaction to the cross slope during walking: the greater the hindfoot valgization on the cross slope, the greater the KAM reduction with AFO (Spearman ρ=0.53, P=.02). The KAM reduction with LWI correlated moderately negatively with the change in hindfoot varus: the greater the hindfoot valgization on the cross slope, the smaller the KAM reduction with LWI (r=−0.31 P=.18). - Conclusions - LWI may be suitable for patients with limited to normal frontal plane ankle mobility. Patients with greater frontal plane ankle mobility benefit most from frontal plane ankle bridging with AFO. Studies with larger samples are necessary.
Gesehen am 21.12.2022